Why am I doing this?: Ambivalence in the context of non-suicidal self-injury - Gray, Nicole (Deviant behavior, 2023)
Ambivalence regarding non-suicidal self-injury (NSSI) is well reported, yet the experience of ambivalence in the context of self-injury remains understudied. Understanding nuances behind the experiences of ambivalence may allow identification of treatment targets, and promote compassion for individuals experiencing confusing competing thoughts, feelings, and desires. We aimed to explore individuals’ personal experiences of ambivalence toward NSSI. In doing so, we hoped to better understand impacts ambivalence has on individuals’ wellbeing and self-injurious behaviors. Semi-structured interviews with undergraduate university students (n = 31, 17-31 years) with a history of NSSI were analyzed using reflexive thematic analysis. Five themes were developed. These themes capture the personal and social functions of ambivalence, as well as the perpetual nature of ambivalence even long after ceasing the behavior. Ambivalence toward self-injury was a common and confusing experience for our participants. Levels of ambivalence toward self-injury fluctuated during the act of self-injury, and over time more generally, and ambivalence in other areas (e.g. self-perception, emotion, social support) was also described. Given the ubiquity of ambivalence in the experience of self-injury, acknowledging ambivalence as a fundamental component of the recovery process could be beneficial for the individual who self-injures, and those supporting them.